Human Trafficking in Ohio Markets, Responses, and Considerations - Wilson, Jeremy M. (RAND Corporation, 2007)
Wilson and Dalton explore the extent and characteristics of human trafficking in Ohio through both a content analysis of newspaper accounts and interviews with criminal justice officials and social service providers. The authors identify and discuss sex-trafficking cases in Toledo and forced-labor cases in Columbus, and compare the two cities' responses to human trafficking. They conclude with suggestions on how these responses might be improved.